KEMAMPUAN SISWA MENERAPKAN KONSEP MATEMATIKA PADA SOAL PERKALIAN KELAS V SEKOLAH DASAR NEGERI 01 ANJONGAN - Lutvia; Yunika Afryaningsih; Rianti Nurdiana (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
The ability to apply concepts in mathematics learning is very important for students to master because it will have an impact on student learning outcomes so that they can be declared to have passed the KKM in mathematics learning. This study aims to describe students' ability to apply concepts to fifth-grade multiplication problems where the ability to apply has two indicators, namely execution and implementation. This study uses the Quantitative Descriptive method. The subjects of the study were 22 fifth-grade students. The results of the study show that students' ability to execute problems is in the high category with an average value of 77.50, while students' ability to implement is in the medium category with an average value of 57.27. This shows that students find it easier to execute problems than to implement problems, especially in contextual essay questions, although the average value on the implementation indicator is lower than execution, but in general students are considered capable of applying mathematical concepts, especially in multiplication operations.